EKSISTENSI PERADILAN ADMINISTRASI DALAM SISTEM NEGARA HUKUM INDONESIA - Astomo, Putera (Jurnal Yuridis, 2014)
Administration of court on Indonesian mentioned Peradilan Tata Usaha Negara(PTUN). PTUN is a justice court on underground Mahkamah Agung. As justice court so PTUN became a judicial power on Indonesian State to remember Indonesian State is law state mention in UUD Tahun 1945. This article to purpose knowledgeabout existence Peradilan Tata Usaha Negara in Indonesian law state system.